Snipe taxonomy based on vocal and non‐vocal sound displays: the South American Snipe is two species. (31st January 2020) - Miller, Edward H.; Areta, Juan Ignacio; Jaramillo, Alvaro; Imberti, Santiago; Matus, Ricardo
Abstract : We analysed breeding sounds of the two subspecies of South American Snipe Gallinago paraguaiae paraguaiae and Gallinago paraguaiae magellanica to determine whether they might be different species: loud vocalizations given on the ground, and the tail‐generated Winnow given in aerial display. Sounds of the two taxa differ qualitatively and quantitatively. Both taxa utter two types of ground call. In G. p. paraguaiae, the calls are bouts of identical sound elements repeated rhythmically and slowly (about five elements per second (Hz)) or rapidly (about 11 Hz). One call of G. p. magellanica is qualitatively similar to those of G. p. paraguaiae but sound elements are repeated more slowly (about 3 Hz). However, its other call type differs strikingly: it is a bout of rhythmically repeated sound couplets, each containing two kinds of sound element. The Winnow of G. p. paraguaiae is a series of sound elements that gradually increase in duration and energy; by contrast,  that of G. p. magellanica has two or more kinds of sound element that roughly alternate and are repeated as sets, imparting a stuttering quality. Sounds of the related Puna Snipe ( Gallinago andina ) resemble but differ quantitatively from those of G. p. paraguaiae . Differences in breeding sounds of G. p. paraguaiae and G. p. magellanica are strong and hold throughout their geographical range. Therefore we suggest that the two taxa be considered different species: G. paraguaiae east of the Andes in much of South America except Patagonia, and G. magellanica in central and southern Chile, Argentina east of the Andes across Patagonia, and Falklands/Malvinas.